Odpowiedzi

2009-09-28T21:42:03+02:00
A=3-2√5 b=2+3√5
a*b= (3-2√5)*(2+3√5)=6+9√5-4√5-30=5√5-24
a+b= 3-2√5+2+3√5=5+√5

przepraszam miało byc
a÷b= 3-2√5÷2+3√5= 3-2√5 (3-2√5)(2+3√5) 6+9√5-4√5-30 5√5-24
______=______________=____________=________
2+3√5 (2+3√5)(2+3√5) 4+6√5+6√5+45 12√5+49
Najlepsza Odpowiedź!
2009-09-28T21:58:36+02:00
A=3-2√5 b=2+3√5
a*b= (3-2√5)*(2+3√5)=6+9√5-4√5-30=5√5-24
a:b= (3-2√5):(2+3√5)=(3-2√5):(2+3√5) razy drugi ulamek(2-3√5):(2-3√5)=
={(3-2√5)(2-3√5)}:(4-45)=(6-9√5-4√5+30):(-41)=(36-13√5):(-41)